INVENTORY MANAGEMENT PRACTICES AND PROFITABILITY OF SELECTED QUOTED FOOD AND BEVERAGE FIRMS IN NIGERIA (UNIZIK Journal of Marketing, 2025)
This study examined the relationship between inventory management practices and financial performance among Nigeria's listed food and beverage companies, with particular emphasis on Flour Mills of Nigeria Plc and Nigeria Breweries Plc. The research specifically assesses the impact of inventory holding costs, ordering costs, and turnover rates on corporate profitability, measured through Return on Assets (ROA). The analysis utilizes seventeen years of secondary data (2008-2024) and employs a combination of descriptive statistics, correlation analysis, and panel regression techniques to evaluate these relationships. The methodological approach ensures robust examination of inventory management's financial implications within Nigeria's food and beverage sector. The results demonstrate that elevated inventory holding and ordering costs adversely affect profitability, while improved inventory turnover exerts a positive influence. These findings underscore that strategic inventory management characterized by enhanced turnover efficiency coupled with cost containment can substantially boost financial performance. The study contributes to existing literature by addressing sector-specific knowledge gaps and provides actionable insights for industry practitioners and policymakers, recommending investments in modern inventory systems, workforce training, and turnover optimization strategies to maximize profitability.
Keywords: Inventory management, profitability, Return on Assets (ROA), inventory costs, ordering costs.